The Analysis of Google Translate in Arabic Fabel Story: A lion and a mouse - Fitriah, Siti; Putri, Aprilia Kartika; Amri, Ulil; Putra, Yoga Mestika (Proceeding International Conference on Malay Identity, 2023)
The main purpose of this research is to analyse the results of translation from Arabic into Indonesian language using machine translation. The machine translation which is used in this research is Google Translation (GT). This machine translation is most popular than many other free machine translations. Moreover, Turovsky, a leader of GT, claimed that there were almost 500 million over the world used GT. The popularity of this machine attracts the researcher to analyse in depth about the language systems produced by GT. The data source is a fabel story in Arabic language entitled (The lion and the mouse). The object of this research is words, phrases, clauses, and sentences. The methodology of this research is qualitative, because the data will be presented in descriptive way. The results of the data show that GT tends to make errors at the semantic level rather than in syntax and morphology. Thus, it shows that transferring messages form source text into target text by using machine translation, GT, tends to be weak. Abstrak Tujuan utama penelitian ini adalah untuk menganalisis hasil penerjemahan bahasa Arab ke dalam bahasa Indonesia dengan menggunakan mesin penerjemah. Mesin penerjemah yang digunakan dalam penelitian ini adalah Google Translate (GT). Google translate adalah salah satu mesin penerjemah yang cukup populer dari sekian mesin penerjemah yang tidak berbayar lainnya. Bahkan Turovsky, selaku leader GT, mengklaim bahwa 500 juta dari penduduk seluruh dunia telah menggunakan produk GT. Kepopuleran mesin ini, membuat peneliti tertarik untuk menganalisis lebih dalam mengenai sistem bahasa yang dihasilkan GT. Sumber data yang dianalisa berupa cerita fabel bahasa arab yang berjudul (singa dan seekor tikus). Objek penelitian berupa kata, frasa, klausa dan kalimat. Metode yang digunakan adalah kualitatif, karena penyajian data akan bersifat deskriptif. Hasil analisis data menunjukkan bahwa GT cenderung lebih banyak melakukan kesalahan pada tataran semantik daripada sintaksis dan morfologi. Hal ini menunjukkan bahwa pentransferan makna atau pesan dari TSU ke dalam TSA menggunakan mesin penerjemah GT cenderung masih lemah.